Using Narrative Case Studies in an Online World Religions Course to Stimulate Deep Learning about Islam - Sherman Lee Elliott (Arizona State University, 2010)
The purpose of this action research was to examine how a narrative case study in an online asynchronous world religions course affected learnersâ understandings, appreciation, and respect for the beliefs and values of others. The world religions course examined a variety of religions including Islam. Ten participants received information about the Five Pillars of Islam; they then analyzed a narrative case study written by the instructor that was a fictional representation centering around the Five Pillars. Following this analysis, learners used the Five Pillars of Islam to construct their own narrative case study. Pre and post assignment data were collected and analyzed. The data sources included: responses to a survey; narrative answers to open-ended questions; written analyses of the narrative case study; responses to telephone interviews; and, written original narrative case studies. Results indicated that learners demonstrated positive changes in their beliefs and attitudes about Islam, and experienced different ways of thinking. In particular, participants demonstrated changes when they: (a) expressed new understandings of Islam as framed through self reflection; (b) compared Islam to a personal prayer life; (c) reflected new appreciations of the Islamic faith; and, (d) recognized stereotypes about Islam. The different ways of thinking that participants experienced occurred when they; (a) created mental images; (b) understood comprehensively and analytically; (c) reflected understandings in constructing an original narrative; (d) applied content to real-life; and, (e) enjoyed analyzing the case. The results of this study were encouraging for this on-line asynchronous course. Others who wish to complete their own action research may consider designing narrative case studies for learners to analyze and inviting them to construct their own narrative case studies. Keywords: Teaching World Religions; Islam; Deep Learning; Narrative Case Studies